Relationship Between Neutrophil-Lymphocyte Ratio Value And Severity of Mitral Stenosis Due to Rheumatic Heart Disease in Outpatients at H. Adam Malik General Hospital Medan - Achmad, Aziz; Safri, Zainal; Haykal, Teuku Bob; Siregar, Abdullah Afif; Akbar, Nizam Zikri; Ardini, Tengku Winda; Andra, Cut Aryfa; Lubis, Anggia Chairuddin (Journal of Society Medicine, 2024)
Introduction: Mitral stenosis (MS) is a heart valve disease characterized by narrowing of the mitral valve, commonly caused by rheumatic heart disease. Accurate evaluation of MS severity is crucial for management, with echocardiography being the gold standard. The Neutrophil-Lymphocyte Ratio (NLR), reflecting inflammation, may correlate with MS severity. This study aims to assess the relationship between NLR values and MS severity due to rheumatic heart disease. Method: This cross-sectional study was conducted at H. Adam Malik General Hospital Medan from January 2023 until the required sample size was achieved. Patients diagnosed with MS by echocardiography based on the American Society of Echocardiography (ASE) criteria were included. Echocardiographic parameters such as mitral valve area (MVA) and mean pressure gradient (MV mean PG), along with blood NLR values, were analyzed for associations. Statistical significance was set at P < 0.05. Results: Significant differences in NLR values were observed between mild-to-moderate MS (1.93; 0.82–10.64) and severe MS (3.56; 1.81–13.08) (P = 0.0001, Mann-Whitney test). An NLR threshold of 2.91 predicted severe MS with 82% sensitivity and 81.8% specificity (P = 0.0001; AUC 0.856; 95% CI 0.772–0.940). Conclusion: NLR strongly correlates with MS severity and serves as a reliable predictor for severe MS in patients with rheumatic heart disease. NLR offers a simple, cost-effective tool for assessing MS severity, complementing echocardiography in clinical practice.